2023
DOI: 10.4254/wjh.v15.i12.1272
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific role of autophagy in the liver and its implications in non-alcoholic fatty liver disease

Sana Raza,
Sangam Rajak,
Rajani Singh
et al.

Abstract: Autophagy, a cellular degradative process, has emerged as a key regulator of cellular energy production and stress mitigation. Dysregulated autophagy is a common phenomenon observed in several human diseases, and its restoration offers curative advantage. Non-alcoholic fatty liver disease (NAFLD), more recently renamed metabolic dysfunction-associated steatotic liver disease, is a major metabolic liver disease affecting almost 30% of the world population. Unfortunately, NAFLD has no pharmacological therapies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…It is important to note that impaired mitochondrial metabolism is widely associated with NAFLD by mediating dysregulation of lipid metabolic homeostasis. The deeper understanding of the molecular structure of mitochondrial plasticity is still in its infancy, but it may provide new doors for the development of future physiological compounds with potential for clinical NAFLD therapy ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that impaired mitochondrial metabolism is widely associated with NAFLD by mediating dysregulation of lipid metabolic homeostasis. The deeper understanding of the molecular structure of mitochondrial plasticity is still in its infancy, but it may provide new doors for the development of future physiological compounds with potential for clinical NAFLD therapy ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an evolutionarily preserved process, autophagy can be found in all the eukaryotic cells including the hepatocytes, where, as a catabolic process, it contributes to the preservation of liver tissue homeostasis in both parenchymal (hepatocytes) and non-parenchymal (Kupffer cells, hepatic stellate cells, and sinusoidal endothelial cells) hepatic cells ( Raza et al, 2023 ). The understanding of cell type-specific autophagy in the liver is important to develop novel focused pharmacological targets for the treatment of liver diseases.…”
Section: Metabolic Liver Diseasesmentioning
confidence: 99%
“…Indeed, it has been demonstrated that defects in autophagy homeostasis (an enhancement or a suppression) facilitate the onset and the development of metabolic disorders, including obesity, diabetes, and metabolic liver diseases ( Kim and Lee, 2014 ; Zhang et al, 2018 ; Raza et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%